Toxoplasma gondii Infection in Immunocompromised Patients: A Systematic Review and Meta-Analysis - Wang, Ze-Dong; Liu, Huan-Huan; Ma, Zhan-Xi; Ma, Hong-Yu; Li, Zhong-Yu; Yang, Zhi-Bin; Zhu, Xing-Quan; Xu, Bin; Wei, Feng; Liu, Quan (Frontiers in Microbiology, 2017)
Toxoplasma gondii has been suggested as an important opportunistic pathogen in immunocompromised patients. We conducted a global meta-analysis to assess the prevalence and odds ratios (ORs) of T. gondii infection in immunocompromised individuals. Electronic databases were reviewed for T. gondii infection in HIV/AIDS patients, cancer patients, and transplant recipients, and meta-analyses were conducted to calculate overall estimated prevalence and ORs using random-effects models. Totally, 72 eligible studies were included. The estimated pooled prevalence of T. gondii infection in immunocompromised patients and the control was 35.9% and 24.7% (p<0.001), with an OR of 2.24, i.e., 42.1% and 32.0% for HIV/AIDS patients and the control (p<0.05), 26.0% and 12.1% for cancer patients and the control (p<0.001), and 42.1% and 34.5% for transplant recipients and the control (p>0.05), whose estimated pooled ORs were 2.03, 2.89, and 1.51 (95% CI, 1.16–1.95), respectively. This study is the first to demonstrate that the immunocompromised patients are associated with higher odds of T. gondii infection, and appropriate prevention and control measures are highly recommended for these susceptible populations.